Cultivation of microalgae in adjusted wastewater to enhance biofuel production and reduce environmental impact: pyrolysis performances and life cycle assessment - Li, Gang; Hu, Ruichen; Wang, Nan; Yang, Tenglun; Xu, Fuzhuo; Li, Jiale; Wu, Jiahui; Huang, Zhigang; Pan, Minmin; Lyu, Tao (Elsevier, 2022)
The interest in microalgae as a renewable and sustainable feedstock for biofuels production has inspired a new focus in biorefinery. Current innovations in microalgae technology include the use of wastewater as the cultivation medium towards nutrients recovery, renewable energy generation, as well as wastewater treatment. Though recent studies have favoured the competitiveness of such an approach, how to maintain a high-quality microalgae-derived biofuel production in real wastewater with fluctuations in nutrient contents is still a challenge. This study investigated a strategy of adjusting the nutrient composition of the feeding wastewater (i.e. anaerobic digestion effluent) for microalgae cultivation (Desmodesmus sp.) and biofuel production. The addition of an appropriate amount of nutrients, including magnesium, iron and phosphorus, significantly enhanced the microalgal biomass production (0.78 g L−1) compared with the original wastewater (0.35 g L−1) and the standard BG11 microalgae cultivation medium (0.54 g L−1). In terms of the potential biofuel quality, the use of adjusted wastewater led to a higher content of valuable products (aliphatic hydrocarbon and fatty acids were accounted for 23.98% and 42.33% of the whole biomass, respectively) along with a reduction in potentially toxic substances (nitrogen-containing compounds and polycyclic aromatic hydrocarbons were accounted for 7.96% and 7.09% of the whole biomass, respectively) compared with the other cultivation groups. Moreover, the lower optimal temperature of pyrolysis engendered by the adjusted wastewater was significant for reduction of process energy consumption, which in turn led to overall lowered environmental impacts (838.52 mPET2000, applying life cycle assessment) than did the original wastewater (1165.67 mPET2000) and standard cultivation medium (1347.63 mPET2000). This study demonstrated that the adjustment of wastewater can act as a potential approach for the improvement in the quality of microalgal biofuel production, with consequent reduced environmental impacts.
Keywords: Circular economy; Environmental sustainability; Microalgal technology; Nutrient neutrality; Nature-based solution; Renewable energy